A 3D analysis of crack-front shape of asymmetric repaired aluminum panels with composite patches - Abdelkader Djebli; El Hadj Besseghier; Mostefa Bendouba; Abdelghani Baltach; Abdelkrim Aid (Fracture and Structural Integrity)
Through this study, a numerical simulation based on 3D in order to investigate the effect of Crack-front shape on the stress intensity factor and fatigue crack growth behavior of center cracked aluminum plate repaired asymmetrically with a bonded composite patch. Consequently, Skew degree is a significant effect on stress intensity factor (SIF) distribution along the crack front in thick panels more than thin panels. Moreover, Fatigue life was calculated using different averages stress intensity factor of patched panel determined from the uniform crack front model and skew crack front model obtained from FEM and when comparing fatigue life values obtained from the finite element model with experimental values were shown a good agreement.